Perbandingan Kemampuan Motorik Dasar Siswa pada Tahun Pertama di SD Unggulan dan Biasa - Kasriman Kasriman (Jurnal Inovasi Pendidikan Dasar, 2018)
The aim of the research was to know the difference of basic motor ability of first year students between ordinary primary school and outstanding primary school in Kecamatan Pasar Rebo Jakarta Timur. The research population was 34 students in grade I SDN Susukan 06 Pagi and 35 students in grade I SDN Cijantung 03. The sample was 60 students from both schools selected by purposive sampling technique. The research instrument was basic motor ability test for grade 1-3 primary students that consisted of 1) Catch a ruler / stick, 2) Stand on one leg, 3) Refuse a ball, 4) Dribble a ball, 5) Hit a dropped ball, 6) Move a marble, 7) Kick a ball, 8) Throw a ball, 9) Run zig zag, 10) Expect to stand, 11) Long jump without prefix, 12) Kissing the knee, 13) Long Relative Physical Activity (15-20 minutes). The data was analyzed by independent sample two test (t-test). The calculation results of t-test obtained tcount = 3.378 at a = 0.05 with n = 30, while ttable = 2.045. It meant that there was a difference of basic motor ability of grade I students between students of SDN Susukan 06 Pagi and students of SDN Cijantung 03 in Kecamatan Pasar Rebo Jakarta timur. The conclution was student basic motor ability of ordinary school was higher than outstanding school.